Program Kemitraan dalam Sistem Pertanian Terpadu - Sahat M. Pasaribu (Analisis Kebijakan Pertanian, 2015)
EnglishCollaboration pattern for productive activities in the form of public - private partnerships in the agricultural sector is very important and could be an alternative program to improve farmer’s income. Public - Private Partnership (PPP) is a policy instrument to gear up rural resources toward competitive produces. This paper describes the concept of partne rships program for integrated farm i ng systems and discusses its development orientation. Nucleus - plasma and sub - contract partnership patterns are mostly suitable for agricultural sector. PPP has its potential to strengthen institutional relationships betwe en the farmers and private sectors through government facilities. PPP should be able to help the farmers to deal with agribusiness financial problems, improve product quality, and increase access to market. Energy and other high economic value products ob tained from this partnerships business activities are expected to support food self - reliance and improve farmer’s welfare.  IndonesiaPola kerja sama untuk kegiatan produktif dalam bentuk kemitraan (public-private partnership atau PPP) di sektor pertanian sangat penting sebagai alternatif program dalam rangka peningkatan pendapatan masyarakat. PPP adalah salah satu instrumen kebijakan yang mampu menggerakkan sumber daya perdesaan untuk menghasilkan produk yang berdaya saing. Makalah ini bertujuan untuk mendeskripsikan konsep program kemitraan untuk sistem pertanian terpadu dan membahas orientasi pengembangannya. Pola kemitraan inti-plasma dan subkontrak dinilai relevan diaplikasikan untuk sektor pertanian. PPP berpotensi memperkuat hubungan kelembagaan antara petani dengan swasta yang difasilitasi pemerintah. PPP dapat membantu petani mengatasi masalah pembiayaan usaha pertanian, memperbaiki kualitas produk, dan meningkatkan akses pasar bagi produk yang dihasilkannya. Energi dan produk bernilai ekonomi tinggi lain yang dihasilkan dengan pola kerja sama ini diharapkan dapat mendukung kemandirian pangan dan meningkatkan kesejahteraan petani.